2006
DOI: 10.1038/sj.onc.1209993
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SOCS1 and SOCS3 genes is differentially regulated in breast cancer cells in response to proinflammatory cytokine and growth factor signals

Abstract: DNA-hypermethylation of SOCS genes in breast, ovarian, squamous cell and hepatocellular carcinoma has led to speculation that silencing of SOCS1 and SOCS3 genes might promote oncogenic transformation of epithelial tissues. To examine whether transcriptional silencing of SOCS genes is a common feature of human carcinoma, we have investigated regulation of SOCS genes expression by IFNc, IGF-1 and ionizing radiation, in a normal human mammary epithelial cell line (AG11134), two breastcancer cell lines (MCF-7, HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 33 publications
7
49
0
Order By: Relevance
“…43 SOCS5 has been shown to be decreased in prostate cancer cell lines compared to a non-malignant prostate cell line. 44 Collectively, these data support the notion that elevation of hsa-miR-141 and hsa-miR-375 in prostate tumors alters gene expression programs, and that identification of their target genes could yield information regarding prostate cancer biology. We are currently undertaking functional studies to investigate whether these miRNAs contribute to disease development and/or progression.…”
Section: Early Detection and Diagnosissupporting
confidence: 61%
“…43 SOCS5 has been shown to be decreased in prostate cancer cell lines compared to a non-malignant prostate cell line. 44 Collectively, these data support the notion that elevation of hsa-miR-141 and hsa-miR-375 in prostate tumors alters gene expression programs, and that identification of their target genes could yield information regarding prostate cancer biology. We are currently undertaking functional studies to investigate whether these miRNAs contribute to disease development and/or progression.…”
Section: Early Detection and Diagnosissupporting
confidence: 61%
“…Indeed, reports describing SOCS-3 hypermethylation and subsequent loss of expression in a variety of cancers support the idea that SOCS-3 may have a tumor-suppressing function (94)(95)(96)(97). In contrast, elevated SOCS-3 expression was reported in human breast cancer and melanoma tissues, as well as in a subset of classic Hodgkin's lymphoma cell lines and primary lymphoma cells (98)(99)(100)(101)(102)(103)(104). In several studies, SOCS-3 promoted cell growth and proliferation in a number of cancers (100,103,105), and elevated levels of SOCS-3 were reported to confer a growth advantage to a melanoma cell line (103).…”
Section: Involvement Of Socs-3 In Gliomasmentioning
confidence: 87%
“…Interestingly, a good correlation between constitutive SOCS 3 expression, lack of its inducibility and IFN cell resistance was obtained in additional melanoma cell lines (Table 1). The strong upregulation of SOCS 3 following IFN-g could be a specific feature of melanoma lineages because epithelial breast cancer cells showed its downregulation (Evans et al, 2007) or variable expression (Souckova, unpublished data). However, in breast cancer cells SOCS 1 was strongly activated while its induction was rather weak in melanoma lines used.…”
Section: Expression Profiles Of Socss In Melanoma Cellsmentioning
confidence: 99%
“…In support, three IFN-insensitive WM 1158R, WM 9 and 1205 Lu melanoma lines had high basal expression of SOCS 3 compared to sensitive cells. Furthermore, breast cancer (Evans et al, 2007) and leukaemia cells (Sakai et al, 2002) showed elevated constitutive expression of SOCS 1 and SOCS 3 and the resistance to proinflammatory cytokines including IFN-g. Perhaps IFN sensitivity of a SOCS 3 promoter is reduced due to aberrant expression of an activatory transcription factor(s). In this context, aberrant activation of tissue-specific promoters has been observed in cancers (Kovarik et al, 1993).…”
Section: Expression Profiles Of Socss In Melanoma Cellsmentioning
confidence: 99%
See 1 more Smart Citation